Outcome of pediatric cardiac surgery and predictors of major complication in a developing country - Indah K Murni; Mulyadi M Djer; Piprim B Yanuarso; Sukman T Putra; Najib Advani; Jusuf Rachmat; Aries Perdana; Rubiana Sukardi (Wolters Kluwer Medknow Publications, 2019)
Background: Evaluating outcome and identifying predictors of major complications among children undergoing cardiac surgery are essential to improve care. We evaluated short-term outcomes of postcardiac surgery and predictors of major complications in a national referral hospital in Indonesia. Methods: A prospective cohort study was conducted from April 2014 to March 2015 on all children undergoing cardiac surgery. Participants were followed up from the time of surgery until hospital discharge and 30-day mortality. We performed univariate and multivariate logistic regression using STATA 12-1 to identify predictors of postsurgical major complications. Results: A total of 257 patients (median age: 36 months) were recruited; 217 (84.1%) had complications, including low cardiac output syndrome (19.8%), arrhythmia (18.6%), sepsis (17.4%), and pleural effusion (14.8%). Forty-nine (19%) patients had major complications, including cardiac arrest (5%), need for emergency chest opening (3.9%), and multiple organ failure (7.4%). 12.8% died during hospital stay, and 30-day mortality was 13.6%. Predictors of major complications were cyanotic congenital heart disease (odds ratio [OR]: 4.6, 95% confidence interval [CI]: 1.5-14.2), longer duration of cardiopulmonary bypass (CPB, OR: 4.4, 95% CI: 1.5-13.4), high inotropes (OR: 13.1, 95% CI: 3.2-54.2), and increase in lactate >0.75 mmol/L/h or more in the first 24 h (OR: 37.1, 95% CI: 10.1-136.3). Conclusion: One-fifth of children undergoing cardiac surgery experienced major complications with around 13% mortality. Cyanotic congenital heart disease, longer duration of CPB, high inotropes on leaving operating theater, and increase in blood lactate are associated with major complications in children after cardiac surgery.